2013
DOI: 10.1002/tesq.126
|View full text |Cite
|
Sign up to set email alerts
|

“Non‐coercive Rearrangements”: Theorizing Desire in TESOL

Abstract: In this article, the authors argue that at the center of every English language learning moment lies desire: desire for the language; for the identities that English represents; for capital, power, and images that are associated with English; for what is believed to lie beyond the doors that English unlocks. However, despite its centrality within TESOL practice, the construct of desire has been largely undertheorized by English language educators. The authors propose (1) that educators in the TESOL field would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 61 publications
0
89
0
Order By: Relevance
“…Having learners analyze and reflect about their own data and discuss them with others in class is also good practice as recent research has suggested (Murphey & Falout, 2010). Finally, I would add that we can ask learners to reflect on the relationship between their own beliefs, emotions, and identities, such as by asking them to work with collages, mini-autobiographies and reflective questions to help them understand their desires and emotions in EFL learning and teaching, as has been suggested by Motha and Lin (2014).…”
Section: Unveiling the Relationship Between Beliefs Emotions And Idementioning
confidence: 99%
See 1 more Smart Citation
“…Having learners analyze and reflect about their own data and discuss them with others in class is also good practice as recent research has suggested (Murphey & Falout, 2010). Finally, I would add that we can ask learners to reflect on the relationship between their own beliefs, emotions, and identities, such as by asking them to work with collages, mini-autobiographies and reflective questions to help them understand their desires and emotions in EFL learning and teaching, as has been suggested by Motha and Lin (2014).…”
Section: Unveiling the Relationship Between Beliefs Emotions And Idementioning
confidence: 99%
“…In language learning, the increasing recognition of the inseparability of emotion and cognition stems largely from a sociocultural approach to these constructs (Imai, 2010;Swain, 2013), from studies based on the biology of cognition originating from the works of biologist Humberto Maturana 11 (Aragão, 2011), and from a more critical/poststructuralist approach to emotions (Benesch, 2012;Motha & Lin, 2014). Aragão (2011), for instance, has argued that the relationship between embarrassment and self-esteem influenced by beliefs associated with a student's self-concept "play[s] a fundamental role in the way students see themselves in class and how they behave in their learning environment" (p. 303).…”
Section: Emotions and Beliefsmentioning
confidence: 99%
“…Such is the global allure of English that, in urban settings at least, few young people enter secondary school without a modicum of desire to learn it, and for many the desire is deeply Farrell (2015) Canadian English as a second language college Not demonstrating mastery of the subject Trang & Baldauf (2007) Vietnamese university students felt and persuasive (Motha & Lin 2014). So, as Littlejohn (2008) has argued, in some ways the English teacher's main task is not to motivate learners but to prevent their DEmotivation, that is, the gradual loss of a pre-existing motivation to learn.…”
Section: Demotivationmentioning
confidence: 99%
“…An enhanced understanding of globalization and neoliberalism will help in the development of research tasks on identity and language education. (Dörnyei & Ushioda 2009;Murray, Gao & Lamb 2011), continues to engage scholars in the field of language education and applied linguistics (Clark 2009;Reeves 2009;Anya 2011;Chang 2011;Mastrella & Norton 2011;Ollerhead 2012;Motha & Lin 2014;Anya 2017) and has now been included in the Douglas Fir Group framework of second language acquisition (SLA) (Douglas Fir Group 2016). In addition to asking 'Are students motivated to learn a language?'…”
Section: Globalization and Neoliberalismmentioning
confidence: 99%